Naked in the Old and the New World: Differences and Analogies in Descriptions of European and American herbae nudae in the Sixteenth Century - Čermáková, Lucie; Černá, Jana (Journal of the history of biology, 2018)
The sixteenth century could be understand as a period of renaissance of interest in nature and as a period of development of natural history as a discipline. The spreading of the printing press was connected to the preparation of new editions of Classical texts and to the act of correcting and commenting on these texts. This forced scholars to confront texts with living nature and to subject it to more careful investigation. The discovery of America uncovered new horizons and brought new natural products, which were exotic and unknown to Classical tradition. The aim of this study is to compare strategies and categories, which were used in describing plants of the Old and the New World. Attention will be paid to the first reactions to the new flora, to the methods of naming and describing plants, to the ways of gaining knowledge about plants from local sources or by means of one's own observation. The confrontation with novelty puts naturalists in the Old World and in the New World in a similar situation. It reveals the limits of traditional knowledge based on Classical authorities. A closer investigation, however, brings to light not only the sometimes unexpected similarities, but also the differences which were due to the radical otherness of American plants.
Keywords: rostliny; History, 16th Century; Books, Illustrated; dějiny 16. století; Botany; Europe; Evropa; botanika; Reference Books; Experience; Natural history; Plants; Herbae nudae; ilustrované knihy; referenční knihy; Classical authorities; Natural History; History of botany; New World; přírodopis